STUDENT SENATE'S COMMUNICATION STYLE ON “SEMA UNIMED” INSTAGRAM: IDENTIFYING FRAMING MESSAGE FOR ACADEMIC POLICIES - Rachel Mutiara Lolita Marpaung; Bella Yanti Marpaung; Rita Hartati (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This research examines how students at Universitas Negeri Medan (UNIMED) express their opinions through Instagram, focusing on the @semaunimed.id account managed by the Student Senate. Using qualitative content analysis, this study explores the themes, communication styles, and emotional framing found in students' comments. The findings show that students often use sarcasm, humor, and informal language to voice their concerns, especially on issues such as academic policies and campus facilities. Sarcasm emerged as the most dominant style (33%), while negative emotional framing appeared in 60% of the analyzed comments, indicating a tendency towards dissatisfaction and criticism. However, positive expressions of support and constructive feedback also appeared. Using the theoretical framework from Norton, Gudykunst, and Entman, this study shows that Instagram not only serves as a platform for informal dialog, but also as a space for advocacy, institutional accountability, and student participation in higher education discourse.